2007
DOI: 10.1038/sj.jp.7211780
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative illness severity and progression from moderate to severe retinopathy of prematurity

Abstract: Objective: To test cumulative neonatal illness severity (IS) and IS fluctuation as predictors of progression from moderate to severe retinopathy of prematurity (ROP).Study Design: Data from research databases and medical record review were collected for infants from four neonatal intensive care unit (NICUs) admitted between 1995 and 2001 and diagnosed with prethreshold ROP. Cumulative neonatal IS measured using daily Scores for Neonatal Acute Physiology (SNAP) for the first 28 days of life, and IS fluctuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
(33 reference statements)
1
16
0
2
Order By: Relevance
“…Use of prenatal corticosteroids did not show any statistical impact on development of ROP, which has not been shown in other studies. 24 The presence of sepsis in our study was considered to be a risk factor for ROP and showed significance. In the literature, this association has already been described.…”
Section: Discussionmentioning
confidence: 99%
“…Use of prenatal corticosteroids did not show any statistical impact on development of ROP, which has not been shown in other studies. 24 The presence of sepsis in our study was considered to be a risk factor for ROP and showed significance. In the literature, this association has already been described.…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjusting for other risk factors, cumulative SNAP was unable to accurately predict the desired outcome (threshold ROP). 26,27 SNAPPE-II has been used as a standard score in the NICU of our Institution since 2004. SNAPPE-II estimates illness severity using nine physiological and laboratory parameters collected within the first 12 h of life of preterm patients.…”
Section: Discussionmentioning
confidence: 99%
“…The research on the various risk factors is extensive in literature. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Finding an easily applicable and noninvasive prognostic model for the expected course of ROP is a keystone in controlling this socially signifi cant disease. This will allow us to focus the limited human and fi nancial resource in Bulgaria on patients at risk.…”
mentioning
confidence: 99%